Vers une signature spatiale de la vulnérabilité épidémiologique en France : l'exemple de la grippe - Benjamin Lysianuk; Martine Tabeaud (Physio-Géo)
The epidemiology of infectious diseases is in the heart of the concerns of numerous authorities of Public health. This theme was reactivated by the anguishes generated by the Severe Acute Respiratory Syndrome (SARS) or more recently by the fears of a flu-like pandemic stemming from an avian origin. The current researches also concern "common" epidemics such as the seasonal flu, generating crisis situations. A better understanding would allow to manage them better and to pull them transferable lessons then in bigger scale threats.The geography took part very early in the debate about diseases but the evolution of its techniques allowed only recently glimpsing its operability in the field of the descriptive epidemiology. While crossing the vision of the risk with the techniques of spatial analysis, the geography can propose a territorialization of the vulnerability factors operating in the flu: a spatialization of a sanitary risk.